(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The contribution evaluates the legal regime and the role of guidelines, tertiary sources and soft law in the framework of flexible legislation, also in the light of the prevailing case law and doctrine. Furthermore, it particularly examines the issue of the legal qualification and effectiveness of clinical practice guidelines, focusing on the relevance of their violation in the judicial field. Furthermore, the historical aspects of the evolution and the growing importance of the maxims of experience in the clinical practice of the doctor from ancient times to the contemporary reality are analyzed in an interdisciplinary perspective.